A CAD-based Algorithm for Solving Stable Parameter Region of Fractional-order Systems with Structured Perturbations - Yang, Jing; Hou, Xiaorong; Luo, Min (Fractional calculus & applied analysis, 2019)
Based on cylindrical algebraic decomposition (CAD) technique, an algorithm for solving the stable parameter region of factional-order systems with structured perturbations (FOSSP) is presented. The algorithm is nonconservative and universal for fractional order systems with order 0 < α < 2. And the computational complexity of the algorithm is less than existing methods. Two examples are given to show the effectiveness of the proposed method.